2018
DOI: 10.3329/jemc.v8i3.38365
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Atorvastatin and Rosuvastatin on Anti- Thrombogenic Effect in Patients with Hyperlipidemia

Abstract: Background: Atorvastatin and rosuvastatin are two widely used HMG-CoA reductase inhibitors (statins). These are used as lipid-lowering drugs to reduce atherosclerosis-induced cardiovascular events. The beneficial effects of statins also involve some lipid-independent mechanisms which include modification of thrombus formation and degradation, alteration in inflammatory response, plaque stabilization and improvement of endothelial function.Objective: To compare antithrombogenic effect of atorvastatin and rosuva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In general, it was mentioned that a decrease in thrombin generation is highly suggestive [18], especially in patients with hypercholesterolemia [19]. Tonu S. et al registered a significant increase in prothrombin time after 8 weeks of treatment with atorvastatin and rosuvastatin in low doses [20]. Fenton et al found out that simvastatin downregulated thrombin generation as prothrombin fragments F1+F2 in the blood plasma of type 2 diabetes patients were lowering after the treatment period [21].…”
mentioning
confidence: 99%
“…In general, it was mentioned that a decrease in thrombin generation is highly suggestive [18], especially in patients with hypercholesterolemia [19]. Tonu S. et al registered a significant increase in prothrombin time after 8 weeks of treatment with atorvastatin and rosuvastatin in low doses [20]. Fenton et al found out that simvastatin downregulated thrombin generation as prothrombin fragments F1+F2 in the blood plasma of type 2 diabetes patients were lowering after the treatment period [21].…”
mentioning
confidence: 99%